Substorms under northward interplanetary magnetic field: Statistical study. Issue 1 (27th January 2013) - Peng, Z.; Wang, C.; Yang, Y. F.; Li, H.; Hu, Y. Q.; Du, J.
Abstract : [1] It was recently noted that substorms can occur even under prolonged northward interplanetary magnetic field (IMF) conditions. Based on the substorm list obtained from the IMAGE spacecraft, we perform a statistical study on the features of substorms during northward IMF interval. The strength of the substorm is represented by the AL index decrease and the total intensity of the auroral bulge. Four main features have been found as follows: (1) Most substorms occur soon after a southward IMF, and intense substorms are more likely to occur for short duration of northward IMF period (2 ~ 5 h), whereas no intense substorms occur after prolonged northward IMF condition. (2) There is a positive correlation between the strength of the substorm and the two solar wind parameters (the IMF | B y | and the solar wind dynamic pressure P d ). (3) The average strength of the substorms during the storm period is much larger than that of the substorms during the period without storm. Meanwhile, nearly all strong storm time substorms occurred either during the intense storm period, or during the late main phase or the early recovery phase of the storm. (4) About half of substorms, either an increase or a decrease in the solar wind dynamic pressure, are found within 30 min preceding each onset time. Such features indicate that the energy stored in the magnetotail during a previous southward IMF period is the main energy source for substorms under northward IMF condition, especially for intense substorms, and both the IMF | B y | and the solar wind dynamic pressure play an important role in the energy accumulation during the northward IMF period. Key points: The energy stored during a previous southward IMF is the main energy source The solar wind dynamic pressure play important role in the energy accumulation Previous energy can remained in the tail as long as 6 hours